The Management Practices of Multipurpose Cooperatives in the First District of Ilocos Sur - Bundoc, Cristina (Social Sciences and Development Review, 2015)
The study determined the management practices of multi-purpose cooperatives in the First District of Ilocos Sur, Region 1. A combination of descriptive, comparative and correlational research designs were used in the study. The respondents of this study were the sixty (65) officers and employees of the eight (8) Multi-Purpose Cooperatives in the First District of Ilocos Sur chosen through random sampling. Results revealed that majority of the officers and employees of the multi-purpose cooperatives belong to the middle-aged group; the multi-purpose cooperatives are dominated by female and married personnel who possess good educational qualifications. The level of management practices of the multi-purpose cooperatives as perceived by their officers follows a pattern wherein planning, organizing, directing and controlling were Very High. The employees of multipurpose cooperatives perceived a High level of management practices along planning, organizing, directing and controlling. The study recommends a systematic development of action programs aimed at reaching agreed business objectives through directing and continuously responding to the challenges of the times. The multi-purpose cooperatives should intensify their communication process by adopting information technology approaches and adopting a system of incentives that could further strengthen the commitment and participation of the administrators, staff and members in the operation of the cooperatives. Furthermore, the multi-purpose cooperatives should strengthen their monitoring, evaluation and reporting system through the strict implementation of the Generally Accepted Accounting Procedures (GAAP) and conduct periodic performance evaluation of officers and employees and exercise promptness in submitting reports to the Cooperative Development Authority.